Analisis Pengaruh Jarak Elektrode terhadap Kinerja Sensor IDE Berlapis Grafit untuk Mengukur Suhu - Doni Bowo Nugroho; Muslimah Dirayati; Dinda Yesi Liswanti Silaban; Rina Oktavia; Osland First Purba (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
This study aimed to investigate the effect of the distance between electrodes on the performance of graphite-coated interdigitated electrode (IDE) sensors for temperature changes measurement. IDE sensors have good potentials in various application due to large surface area, low cost, versatility, and customizable geometry. Furthermore, graphite have good thermal conductivity, adequate stability, and easy availability so that the combination of IDE sensor and graphite is very potential to be used as a temperature sensor. This study focused on IDE sensors that were made in two variations, namely one sensor with an electrode distance or spacing of 0.45 mm and the other sensor 1.00 mm. Graphite solution was made with epoxy. Then, it coated on the sensor using a dip coating technique. The sensor response was tested by observing the change in resistance to temperature variations between 30°C and 50°C. The results showed that the resistance of sensor decreased with increasing temperature. This showed the tendency of the sensor to the thermistor type of sensor with a negative temperature coefficient (NTC). The sensor with an electrode distance of 1.00 mm showed higher sensitivity and responsiveness with a temperature coefficient of resistance (TCR) or α of -0.045%/K and a material constant (β) of 8534.66 K. Meanwhile, the sensor with an electrode spacing of 0.45 mm had a TCR of -0.04%/K and a β of 8577.87 K. These results indicated that the distance between electrodes affected the sensitivity and responsiveness of graphite-coated IDE sensors in measuring temperature. Keywords: graphite, interdigitated electrodes, temperature sensor.